DECOLONISATION IN AFRICAN POLITICAL THOUGHT - FISHER Augustus Olukayode; OLUDEMI Akintayo Shoboyejo; ADEBOGUN, Babatunde Olayinka (Information Technology and Science (ITScience), 2022)
In essence, African political thought evolved as a result of colonialism and the anti-colonial reactions of first-order African elites. The debate among the episodic and the epochal school of thought over the place of colonialism in African political thought suggests that it took colonialism to inform the people of the continent that they were Africans. Also that Africa had a glorious pre-colonial past. It offered the diverse peoples of the continent a rallying point for unity. This unity was the basis of the anti-colonial reactions especially in the decade before political independence in Africa. This work attempts to examine the origin of African political thought, and the decolonization process in selected regions of the continent namely North-West Africa (Tunisia and Morocco) and British West-Africa. The main source of data collection depends on secondary materials